Pernikahan Dini Menghambat Pertumbuhan Pada Anak Usia 2 Tahun - Hasniati, Hasniati; Syahriani, Syahriani; Nurbaya, Siti; Fitriani, Fitriani; Asnuddin, Asnuddin (Jurnal Kebidanan Malakbi, 2023)
Early marriage, which is marrying children who are still under 20 years old, shows the immaturity of parents' thinking. This situation triggers a parental problem-solving response based on immature thinking. Growth is an increase in the size and number of cells, as well as intercellular tissue, which means an increase in physical structure so that weight (kg) length (cm) and head circumference (cm) can be measured. This study aims to find out "The relationship between early marriage and the growth of children aged 2 years in the working area of the Pammana Public Health Center, Wajo Regency in 2022. The research design used was a cross-sectional study with an observational type. This study uses a total sampling with 30 respondents processing data with Microsoft Excel and SPSS. There is a relationship between early marriage and the growth of children aged 2 years with the results of the chi-square test p = 0.007 and <0.05. There is a relationship between early marriage and the growth of children aged 2 years in the work area of the Pammana Health Center, Wajo Regency in 2022, where the younger the age of marriage, the more susceptible to child growth disorders. So it is hoped that integrated care and supervision health services can be implemented to reduce the risk of early marriage and growth disorders in children.